Modular design of bi- and multi-specific knob domain fusions - Kuravsky, Mikhail; Gibbons, Glyn F.; Joyce, Callum; Scott-Tucker, Anthony; Macpherson, Alex; Lawson, Alastair D. G. (Frontiers in Immunology, 2024)
Here, we report the design of bi-and trispecific antibody fragments with molecular weights as low as 14.5 and 22 kDa. This has been achieved through engineering bovine ultra-long CDR H3 (knob domain peptide) modules with artificial coiled-coil stalks derived from Sin Nombre orthohantavirus nucleocapsid protein and human Beclin-1. The individual modules retain high, independent antigen binding affinity, exhibit exceptional levels of thermal stability, and can be readily joined head-to-tail yielding the smallest described multispecific antibody format. The resulting constructs are also capable of simultaneous binding to all their targets. Furthermore, they can be easily produced at high yield as recombinant products and are free from the heavy-light chain mispairing issue. Compared to existing bispecific formats, the reduced molecular weight of the knob domain fusions may facilitate binding to cryptic epitopes that are inaccessible to conventional antibodies and enable enhanced tissue penetration. Taken together, our approach offers an efficient route to modular construction of minimalistic bi-and multispecifics, thereby broadening the therapeutic scope for knob domain peptides.